2010
DOI: 10.1155/2010/749401
|View full text |Cite
|
Sign up to set email alerts
|

The Avian Proghrelin System

Abstract: To understand how the proghrelin system functions in regulating growth hormone release and food intake as well as defining its pleiotropic roles in such diverse physiological processes as energy homeostasis, gastrointestinal tract function and reproduction require detailed knowledge of the structure and function of the components that comprise this system. These include the preproghrelin gene that encodes the proghrelin precursor protein from which two peptide hormones, ghrelin and obestatin, are derived and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…The gene of this variant is expressed in almost all tissues of chickens, and the expression pattern is almost identical to that of GHS-R1a (Geelissen et al 2003, Tanaka et al 2003, Richards & McMurtry 2010. Other splice variants, the GHS-Rtv and GHS-Rtv-like receptor, show a limited and specific expression in the ovary of chickens (Sirotkin et al 2006) and in the proventriculus and gizzard of the Japanese quail (Kitazawa et al 2009) respectively.…”
Section: Distribution Of the Ghrelin Receptors And The Difference Betmentioning
confidence: 88%
See 1 more Smart Citation
“…The gene of this variant is expressed in almost all tissues of chickens, and the expression pattern is almost identical to that of GHS-R1a (Geelissen et al 2003, Tanaka et al 2003, Richards & McMurtry 2010. Other splice variants, the GHS-Rtv and GHS-Rtv-like receptor, show a limited and specific expression in the ovary of chickens (Sirotkin et al 2006) and in the proventriculus and gizzard of the Japanese quail (Kitazawa et al 2009) respectively.…”
Section: Distribution Of the Ghrelin Receptors And The Difference Betmentioning
confidence: 88%
“…In addition, the ghrelin receptor gene expression has also been detected in various amounts in more or less all peripheral tissues, such as the eyes, heart, thymus, liver, stomach, intestine, spleen, gill, gall bladder, muscle, kidney, head kidney, Brockmann bodies, skin, muscle, and gonads for fish , Chen et al 2008, Kaiya et al 2009a,b, Small et al 2009, Cruz et al 2010, the stomach and gonads, and to a lesser extent in the small and large intestines, adrenal gland, and kidney in frogs (Kaiya et al 2011a), and the heart, lung, thymus, liver, spleen, pancreas, gastrointestinal tract, adrenal gland, kidney, gonads, breast muscle, subcutaneous fat, leg muscle, abdominal fat, and uropygial gland in birds (Geelissen et al 2003, Tanaka et al 2003, Saito et al 2005, Richards et al 2006, Kitazawa et al 2009, Nie et al 2009). In birds, strain differences (Geelissen et al 2003, Tanaka et al 2003, Richards & McMurtry 2010) and a regionspecific expression in the gastrointestinal tract (Kitazawa et al 2009) have been reported. In summary, these data indicate that ghrelin acts on various organs in nonmammalian vertebrates as it does in mammals.…”
Section: Distribution Of the Ghrelin Receptors And The Difference Betmentioning
confidence: 99%
“…The central and peripheral regulatory mechanisms in energy homeostasis, including feed intake and energy expenditure, in avian species have been recently extensively studied (Richards, 2003;Richards and McMurtry, 2010). Many of neural and endocrine mechanisms identified in mammals as involving in regulation feed intake also have this function in birds.…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral or intracerebroventricular (ICV) injection of ghrelin potently stimulates food-seeking behaviours and intake in rodents (Tschop et al, 2000) and intravenous infusion of ghrelin increases energy intake in obese and lean humans (Druce et al, 2005). Surprisingly, in contrast to mammals where ghrelin is orexigenic, in birds, such as the chicken and Japanese quail, ghrelin represses appetite (reviewed in Kaiya et al, 2013b;Richards and McMurtry, 2010). We envisage that ghrelin is anorexigenic in all birds, however, most studies have been performed in poultry and studies in wild birds are lacking (Kaiya et al, 2013b).…”
Section: Resultsmentioning
confidence: 99%